PERTANGGUNG JAWABAN PIDANA KURATOR PELAKU PENGGUNAAN SURAT PALSU DALAM PENGURUSAN HARTA PAILIT. - Sahrul, Ibnu Ibrahim; Candra, Tofik Yanuar; Pandiangan, Roni (SENTRI: Jurnal Riset Ilmiah, 2024)
An analysis of the criminal liability of curators involved in the use of forged letters in the management of bankruptcy property highlights the legal responsibility that must be borne by them for such actions. Focusing on criminal and civil legal aspects, this analysis aims to establish justice, maintain transparency, and protect the interests of all parties involved in bankruptcy proceedings. By establishing appropriate legal consequences, this analysis also plays a role in providing a deterrent effect as well as preventing the recurrence of similar violations in the future, thus maintaining the integrity of the bankruptcy law system.Top of Form The method used in this study is normative juridical legal research, conducted by examining library materials or secondary data only, supported by interviews. The approaches in this study include the legislative approach, the conceptual approach, the analytical approach, and the case approach. The sources of legal material in this study are primary, secondary, and tertiary legal sources, with the collection technique involving the identification and inventory of positive legal rules, examination of library materials, and analysis of legal material sources through systematic and analogous legal interpretation. The result of this study is that criminal acts by the curator in the management of bankruptcy property must pay attention to two functions of criminal law: as law enforcement and Norm enforcement. The curator must be independent and comply with the requirements of legal regulations; otherwise, it can be replaced by a supervisory judge. They must also uphold the principles of honesty and openness. Criminal liability curators who use fake letters emphasize the importance of ethics and professionalism, and can lead to legal consequences both criminal and civil if there is abuse of authority.